3T MRI signal intensity profiles and thicknesses of transient zones in human fetal brain at mid-gestation. (November 2021) - Pogledic, Ivana; Schwartz, Ernst; Bobić-Rasonja, Mihaela; Mitter, Christian; Baltzer, Pascal; Gruber, Gerlinde Maria; Milković-Periša, Marija; Haberler, Christine; Bettelheim, Dieter; Kasprian, Gregor; Judaš, Miloš; Prayer, Daniela; et al.
Abstract: In this study we compare temporal lobe (TL) signal intensity (SI) profiles, along with the average thicknesses of the transient zones obtained from postmortem MRI (pMRI) scans and corresponding histological slices, to the frontal lobe (FL) SI and zone thicknesses, in normal fetal brains. The purpose was to assess the synchronization of the corticogenetic processes in different brain lobes. Nine postmortem human fetal brains without cerebral pathologies, from 19 to 24 weeks of gestation (GW) were analyzed on T2-weighted 3T pMRI, at the coronal level of the thalamus and basal ganglia. The SI profiles of the transient zones in the TL correlate well spatially and temporally to the signal intensity profile of the FL. During the examined period, in the TL, the intermediate and subventricular zone are about the size of the subplate zone (SP), while the superficial SP demonstrates the highest signal intensity. The correlation of the SI profiles and the distributions of the transient zones in the two brain lobes, indicates a time-aligned histogenesis during this narrow time window. The 3TpMRI enables an assessment of the regularity of lamination patterns in the fetal telencephalic wall, upon comparative evaluation of sizes of the transient developmental zones and the SI profiles of different cortical regions. A knowledge of normal vs. abnormal transient lamination patterns and the SI profiles is a prerequisite for further advancement of the MR diagnostic tools needed for early detection of developmental brain pathologies prenatally, especially mild white matter injuries such as lesions of TL due to prenatal cytomegalovirus infections, or cortical malformations. Highlights: The transient zones of the temporal and frontal lobes were correlated in pMRI and histological slices of the same brains. The absolute and relative thicknesses of the zones were measured in pMRI and corresponding HE histological scans. The pMRI signal intensity profiles correlate well with the distribution of the transient zones. The temporal and frontal lobe corticogenesis is temporally and spatially synchronous during 19 to 24 GW.